“Bronquinho”: a low-cost alternative for fat grafting in breast reconstructions within the Brazilian Unified Health System - França, Manuela Bezerra e Silva; Lima, Bruno Oliveira de Sousa; Silva, Isabelle Vitória Rocha da; Carvalho, Mateus Balbino Barbosa de; Sauaia, Brunno Braga; Alves, Érik Victor da Silva; Sampaio, Yasmin Andrade; Oliveira, Ana Gabriela Caldas (Mastology, 2026)
Objective: To describe a low-cost alternative for fat grafting in breast reconstructions within the Brazilian Unified Health System (SUS). Methods: This study presents a descriptive analysis of an alternative technique for adipose tissue collection in reconstructive surgeries. Results: Autologous fat grafting is widely employed in reconstructive surgeries following cancer treatment, owing to its capacity to correct irregularities and restore tissue integrity. It improves functional and aesthetic quality of life in post-mastectomy patients. The conventional technique involves liposuction from a donor site using a 60 mL syringe coupled with a liposuction cannula. Negative pressure is generated by the manual movement of the syringe plunger by the operating surgeon. Subsequently, fractionated fat is retro-injected into the subcutaneous tissue of the reconstruction site. However, the cost of materials, prolonged surgical duration, and consequent surgeon fatigue pose significant challenges. The “bronquinho,” a medical device typically utilized for airway secretion collection during bronchoscopies and endoscopies, can also generate a negative pressure system without requiring manual actuation. This allows for spontaneous, atraumatic fat aspiration, contributing to the preservation of adipocytes. Furthermore, it is economically accessible. Conclusion: Considering the aesthetic and regenerative advantages of fat grafting, the application of the bronquinho in breast reconstruction fat grafting presents a promising alternative. This method optimizes surgical time, reduces surgeon physical strain, and demonstrates good efficacy and safety. Additionally, its affordability makes it suitable for patients within the SUS. Further research is warranted to validate the effectiveness of this technique in this context.